The forgotten Wau: Preserving the tradition/ S’harin Mokhtar and Farah Amira Idris - Mokhtar, S’harin; Idris, Farah Amira (Universiti Teknologi MARA, Perak, 2024)
Traditional games in Malaysia hold a special place in the country’s rich cultural heritage. These games are not only a source of entertainment but also a reflection of Malaysia’s diverse ethnic backgrounds and traditions. However, in today's era, traditional games are increasingly marginalized by society. Due to this, the purpose of this study is to preserve the information and knowledge of traditional games in Malaysia-Wau by analysing the rules, history, and cultural significance of the game. The findings will be used to revive the traditional game by adapting innovation and creativity that suit contemporary tastes to ensure that Wau continues to be enjoyed by current and future generations.